The Bankruptcy Legal Politics in Indonesia based on Justice Value - Ria Sintha Devi; Nanci Yosepin Simbolon; Lestari Victoria Sinaga; Muhammad Yasid (JURNAL AKTA, 2022)
The purpose of this study is to find out and analyze the politics of bankruptcy law in Indonesia based on Justice Value, and the problems that occur in its application. The approach method in this study uses a normative juridical approach. The application of legal politics with the concept of justice in the settlement of bankruptcy cases can be interpreted as a condition where the debtor stops paying his debts that have matured so that by the decision of the Commercial Court his assets are declared as general confiscation to be sold by the curator and distributed to his creditors in a fair and balanced manner according to the proportion with the supervision of the supervisory judge. The confiscation is carried out to ensure the interests of all creditors and prevent executions that are requested by individual creditors. Bankruptcy only concerns the general confiscation of the assets of the bankrupt debtor, excluding civil rights outside of property law, civil rights, public rights and social rights in social life in society.